Implementasi Metode Belajar Melalui Olahraga dalam Pengembangan Motorik Anak Usia Dini - Vicha Kholifatul Aulia; Rivan Saghita Pratama (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article explores the implementation of learning methods through exercise in the motor development of early childhood. The research is conducted through a literature review to examine how exercise contributes to the development of both gross and fine motor skills in children. Well-designed exercise routines not only enhance physical health but also support cognitive and emotional development. The article identifies various types of exercise suitable for young children, as well as challenges and solutions in its implementation. Findings suggest that a holistic approach and consistent support from educators and parents are crucial for maximizing the benefits of exercise in early childhood education. With the right strategies, exercise can become an integral component in supporting children's growth and development.